Fear, Bullying & Will of Female Students in STEM: Case Study of Vocational Schools in Jakarta - Candraningrum, Dewi; Dhewy, Anita (Jurnal Perempuan, 2016)
Women in STEM (Science, Technology, Engineering and Mathematics) continued to decline from secondary schools to universities level, as well as in lab, teaching and research policy-making and technology. This is triggered by the absence and minority of women in policy and decision-making regarding research in science and technology. Women’s leadership is very low in the area of energy use, adaptation to climate change, and economic production. In the formal sector, only 10% of women are in the sector of STI (science, technology, innovation). Only 5% of women who become members of the national academy of science technology in the respective disciplines. Why does it happen? This paper studies several vocational schools in Jakarta to answer those questions. This research found that the fear of a mother and daughter against STEM is not just happening today, but deeply rooted in the tradition, even in modern era. Besides bullying both in school and in the community, girls’ interest in STEM is also still very low compared to boys. However, this study found how girls copes those hindrances with strong will via their agency to win STEM in their education pathways.